The complete chloroplast genome of Osmanthus serrulatus rehd., a natural sweet olive endemic to China. Issue 2 (3rd July 2019) - Chen, Lin; Li, Longna; Pan, Tingting; Yi, Xiangui; Wang, Xianrong; Li, Mingzhi
Abstract: Osmanthus serrulatus is an endemic tree in southwest China. Here, the complete chloroplast genome of this species was assembled and characterised from high-throughput data. The entire circular genome of O. serrulatus was 155, 465 bp in size, which composed of large single-copy (LSC) and small single-copy (SSC) regions of 86, 545 bp and 17, 494 bp, respectively, and separated by a pair of inverted repeat (IR) regions of 25, 713 bp each. The genome contained 133 genes, including 88 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The overall GC content of the genome is 37.8%. A phylogenetic tree reconstructed by 35 chloroplast genomes reveals that O. serrulatus is most related with O. yunnanensis .